Epigenetic Control of Alveolar Macrophages: Impact on Lung Health and Disease - Nirmal Parajuli; Kalpana Subedi; Xzaviar Kaymar Solone; Aimin Jiang; Li Zhou; Qing-Sheng Mi (Cells)
Alveolar macrophages (AMs) are immune cells located in the alveoli—the tiny air sacs in the lungs where gas exchange occurs. Their functions are regulated by various epigenetic mechanisms, which are essential for both healthy lung function and disease development. In the lung’s microenvironment, AMs play critical roles in immune surveillance, pathogen clearance, and tissue repair. This review examines how epigenetic regulation influences AM functions and their involvement in lung diseases. Key mechanisms, such as DNA methylation, histone modifications, and non-coding RNAs, regulate gene expression in response to environmental signals. In healthy lungs, these modifications enable AMs to quickly respond to inhaled threats. However, when these processes malfunction, they could contribute to diseases such as pulmonary fibrosis, COPD, and pulmonary hypertension. By exploring how epigenetic changes affect AM polarization, plasticity, and immune responses, we can gain deeper insights into their role in lung diseases and open new avenues for treating and preventing respiratory conditions. Ultimately, understanding the epigenetic mechanisms within AMs enhances our knowledge of lung immunology and offers potential for innovative interventions to restore lung health and prevent respiratory diseases.